Fish-food interaction network around cage fish farming in a neotropical reservoir - Brandão,Heleno (2021)
Abstract: Aim Investigating whether wild fish accept residual ration from cage fish farming to the point of changing their diet and the fish-food interaction network. Methods The diet of fish species, Astyanax lacustris, Iheringichthys labrosus, Leporinus amblyrhynchus, Schizodon nasutus and Steindachnerina insculpta, bred in Chavantes Reservoir, Upper Paraná basin, was evaluated. Samples were collected on a monthly basis - from March 2008 to February 2009 - around the cage fish farming (NC) and in a reference site (RS) free from the influence of the fish farming activity. Results were analyzed through graphs and metrics of complex network analysis, and Permutational analysis of variance. Results The total number of 641 individuals belonging to all five fish species were collected, 292 in NC and 349 in RS. The total amount of food items consumed by them comprised 24 items in NC and 22 items in RS. The fish-food interaction network has shown nested pattern in the two evaluated areas, which evidenced the generalist structure of this interaction. Connectance values and mean degree of interaction networks were low. Detritus was the most representative item consumed in both sampling sites. Three of the five evaluated species (A. lacustris, S. nasutus and I. labrosus) had residual ration in their diet. Residual ration was the fourth most consumed item in NC. It was also the most representative food item for A. lacustris and S. nasutus. Conclusions Results have shown that cage fish farming activity can influence trophic interactions in aquatic systems, as well as evidenced the ability of S. nasutus, L. labrosus and A. lacustris to take advantage of new food items in their environment.